Exercise Mediates Heart Protection via Non-coding RNAs - Zhang, Yuelin; He, Nana; Feng, Beili; Ye, Honghua (Frontiers in Cell and Developmental Biology, 2020)
Cardiovascular diseases (CVDs) have become the central matter of death worldwide and have emerged as a notable concern in the healthcare field. There is accumulating evidence that regular exercise training can be as a reliable and widely favorable approach to prevent the heart from cardiovascular events. Noncoding RNAs (ncRNAs) could act as innovative biomarkers and auspicious therapeutic targets to reduce the incidence of CVDs. In this review, we summarized the regulatory effects of ncRNAs in the cardioprotection provided by exercise to assess potential therapies for CVDs and disease prevention.